Sustainable academic performance in higher education: a mixed method approach. Issue 4 (3rd April 2022) - Hossain, Syed Far Abid; Xi, Zhao; Nurunnabi, Mohammad; Anwar, Bilal
ABSTRACT: The key purpose of this research is to discuss the role of trajectory movements from education and awareness of sustainability perspective in the higher educational sector. The study analyzes how the trajectory movement of students in various academic places of their interest influences sustainable academic performance. A person-administered survey approach was conducted initially followed by a focus group interview. The results of this research revealed that there are innumerable differences among university learners in terms of trajectory movement, and most of the students care only about a few common learning places like classrooms or laboratories. However, there are other trajectory movements that directly or indirectly influence sustainable academic performance. The research findings suggest that students and academicians are aware of not only the frequent trajectory movements, such as in the classroom, laboratory, and library but also the other trajectory movements inside and outside the campus which may severely affect sustainable academic performance. This study focuses on discovering the relationship between university students' trajectory movement tendencies and sustainable performance in higher educational institutions to fulfill sustainable development goals and how trajectory movements affect students' educational performance in various ways to ensure a better academic outcome for sustainable development.